O fenômeno dos blogs de moda: um estudo de caso - Blog Moda Para Usar - Ruiz, Renata Massignan (2014)
Fashion blogs have fundamentally changed the way which readers accessed information. The analysis and monitoring of one of the pioneers in this blogs market is the object of this study, evaluating, in parallel, one hundred and thirty blogs analysing the way which social media behaved during the period between the years 2006 to 2012. This research begins with a case study of the blog Moda Para Usar, through categorization of fashion and beauty blogs based on their editorial guidelines